Global Value Chains and Product Differentiation: Changing the Politics of Trade. (27th November 2018) - Baccini, Leonardo; Dür, Andreas
Abstract: Both global value chains and trade in differentiated goods have become increasingly important in the international economy. We argue that these two developments interact in changing the political economy of trade. For finished goods, product differentiation facilitates trade liberalization because the adjustment costs of liberalization are lower when countries trade varieties of the same good. By contrast, for goods that are used as inputs in the production process, product differentiation makes trade liberalization more difficult. We find support for this argument in two tests. On the one hand, we look at patterns of lobbying on US preferential trade agreements (PTAs). On the other hand, we use a data set with highly disaggregated tariff data from 61 PTAs signed between 1995 and 2013. The paper contributes to the long‐standing debates on endogenous tariff formation and the consequences of intra‐industry trade, and a nascent literature on the relationship between global value chains and trade policy. Abstract : Global value chains do not unambiguously strengthen support for international institutions. In the presence of product differentiation, they go hand‐in‐hand with more protectionist sentiments and hence less ambitious trade agreements.